2012
DOI: 10.1158/1078-0432.ccr-11-3169
|View full text |Cite
|
Sign up to set email alerts
|

Epstein-Barr Virus Infection and Expression of B-cell Oncogenic Markers in HIV-Related Diffuse Large B-cell Lymphoma

Abstract: Background Epstein-Barr virus (EBV)-mediated lymphomagenesis in the setting of HIV infection has been widely accepted. However, little is known about how EBV impacts prognosis. We investigated the hypothesis that EBV infection is associated with expression of specific B-cell oncogenic markers in HIV-related diffuse large B-cell lymphoma (DLBCL), and examined the prognostic utility of detecting EBV infection. Study Design HIV-related DLBCL cases diagnosed between 1996–2007 within Kaiser Permanente California … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
50
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(52 citation statements)
references
References 37 publications
0
50
2
Order By: Relevance
“…NHL comprises many subtypes, each with distinct epidemiology, etiology, and features (ie, morphology, immunophenotype, and clinical manifestations) 59,60. Epstein–Barr virus (EBV) has been implicated in the development of many NHL subtypes in HIV-infected individuals 61. NHL is the second most common malignancy in HIV-infected patients, with diffuse large B-cell lymphoma (DLBCL) as the most common subtype of HIV-associated NHL (HIV-NHL) followed by Burkitt’s lymphoma (BL) 62…”
Section: Hiv-associated Nhl and Its Problems In Diagnosismentioning
confidence: 99%
“…NHL comprises many subtypes, each with distinct epidemiology, etiology, and features (ie, morphology, immunophenotype, and clinical manifestations) 59,60. Epstein–Barr virus (EBV) has been implicated in the development of many NHL subtypes in HIV-infected individuals 61. NHL is the second most common malignancy in HIV-infected patients, with diffuse large B-cell lymphoma (DLBCL) as the most common subtype of HIV-associated NHL (HIV-NHL) followed by Burkitt’s lymphoma (BL) 62…”
Section: Hiv-associated Nhl and Its Problems In Diagnosismentioning
confidence: 99%
“…Differences in DLBCLs occurring in HIV+ patients when compared to DLBCL occurring in immunocompetent individuals include more frequent extranodal presentation, a larger proportion of the germinal center subtype and a more common association with EBV in HIV (30% vs. <5%). One recent study of 70 AIDS-related DLBCL showed that EBV positivity was independently associated with a higher 2-year overall mortality, and recommended incorporating EBV status with IPI in prognostic categorization (16), although this association has not been found in other studies (13). …”
Section: Introductionmentioning
confidence: 99%
“…In addition AIDS-DLBCLs had more common MYC rearrangements, reduced CD4+ and FOXP3+ T cells, as well as increased activated cytotoxic cells and higher blood vessel density. The presence of EBV in AIDS-related DLBCL has been reported to be associated with a worse clinical outcome (45, 46), but this was not found in a different cohort (41). …”
Section: Text Of Reviewmentioning
confidence: 93%